Architecture of software based on integrated objects - Sokolov, Volodymyr (Collection "Information Technology and Security", 2017)
The paper presents an architecture of software consisting of objects capable of direct interaction by the formation of active dynamic connections, which can be atomic or integral objects. It has been determined that any combination of objects, like atoms, has valency- the ability to form connections, and can be encapsulated into a class of connection. The principles on which the proposed architecture is based are formulated, such as the existence of an atomic basis on architecture, the encapsulation of connectors in components, integration as the basic principle of constructing a component hierarchy, the prohibition of inheritance of component classes at the atomic and higher levels, and the descriptiveness of component structures. It is shown that the formation of new derivative classes in the form of atomic connections can be considered an integration, whose degree depends on the level of integration of the constituent objects. The hierarchy of classes on the basis of integration without inheritance allows using a unified mechanism for both class creation and interaction of objects. As a result of the research, a universal mechanism for constructing integrated objects was developed through a descriptor that contains a complete description of the structure of the object, that allows to use the universal function of synthesizing the connections of all integral objects. It is substantiated that the resolving of any task can be considered as a process of synthesis of a descriptor of an integrated object. The questions of static and dynamic behavior of integrated objects are considered, a two-stage approach to the creation of an integral object was developed by creating an initial proto-object with the subsequent construction of a complete object, which enables the delayed and partial creation of an integrated object when used in the program. It is determined that during program execution the structure of an integrated object is functionally equivalent to the complete disintegrated of an object to an atomic level, which allows to explicitly transform integral objects into atomic connections. Isomeric classes of objects are considered which can change the structure of the connection at run time, leaving the external interface unchanged. As a description of the architecture, a graphic form, a formula of connection that reflects the composition of the integral object and the degree of integration, an atomic formula of connection that reflects the actual structure of the integrated object from the atoms, and a structural formula that reflects the order of connecting objects in the connection are selected. It is shown that for such architecture it is possible to apply operations over configuration both statically and dynamically.